Myrislignan Induces Redox Imbalance and Activates Autophagy in Toxoplasma gondii - Zhang, Jili; Chen, Jia; Lv, Kun; Li, Bing; Yan, Biqing; Gai, Lei; Shi, Chaolu; Wang, Xinnian; Si, Hongfei; Zhang, Jiyu (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii (T. gondii) is an important health problem in human and animals, and the highlighting side effects of launched therapeutic chemicals cannot be ignored. Thus, it is urgent to develop new drugs to against the infection. Myrislignan originated from nutmeg exhibited excellent anti-T. gondii activity in vitro and in vivo, and was able to destroy mitochondrial function. However, the exact mechanism of action is still unknown. In this study, combining RNAs deep-sequencing analysis and surface plasmon resonance (SPR) analysis, the differentially expressed genes (DEGs) and high affinity proteins suggested that myrislignan may affect the oxidation-reduction process of T. gondii. Furthermore, the upregulating ROS activity after myrislignan incubation verified that myrislignan destroyed the oxidant-antioxidant homeostasis of tachyzoites. Transmission electron microscopy (TEM) indicated that myrislignan induced the formation of autophagosome-like double-membrane structure. Moreover, monodansyl cadaverine (MDC) staining and western blot further illustrated autophagosome formation. Myrislignan treatment induced a significant reduction in T. gondii by flow cytometry analysis. Together, these findings demonstrated that myrislignan can induce the oxidation-reduction in T. gondii, lead to the autophagy, and cause the death of T. gondii.